DIFFERENTIAL ACTIVITY OF PEROXIDASES AND LACCASE OF GUT ISOLATED STRAINS IN THE CHANGING OF TEMPERATURE AND PH (Journal of Engineering and Health Sciences, 2019)
Peroxidases (Lignin Peroxidase (LiP) and Manganese Peroxidase (MnP)) and laccase (Lac) are extracellular enzymes that related to lignin degradation. A number of conditions have been designated to increase or inhibit these enzymes’ activities in bacteria. The physical parameters such as pH and temperature are primary importance to enhance the performance of peroxidase and laccase activity. This is due to economy impact and its practicability in the industrial process.  The main objective of this research was to identify individual gut bacterial strains; Klebsiella sp., Serratia sp., Pseudomonas sp. and Enterobacter sp. with maximal peroxidases and laccase enzymes activity manipulative conditions of temperatures and pHs. Enzyme activity assays were conducted for LiP, MnP and Lac using different substrates to specifically measure the activity in all four species. All the recorded data were then analyzed using ANNOVA to demonstrate the significant effect of different temperatures and pHs conditions on enzymes activities in all four species. The results show the optimum temperature for LiP and Lac was 40ºC while for MnP is 30ºC while for pH, LiP and Lac were optimum at pH6 and pH7. Also, among all four species, Enterobacter sp. gives the highest performance in both peroxidases and laccase in response to the change of pH and temperature. Then followed by Pseudomonas sp. and Serratia sp. where the enzymes activity in peroxidases and laccase are above average. Klebsiella sp. demonstrates poor performance below average in peroxidases and laccase. In conclusion, individual species has unique response to the changing pH and temperature which provides optimal activity within the gut.